Tinjauan Yuridis Terhadap Pembagian Harta Waris Kepada Ahli Waris Yang Beda Agama Melalui Wasiat Wajibah - Styawan, Sofyan Adhi; , Mutimatun Ni'ami, S.H., M.Hum (2016)
The purpose of this paper is to determine the position of heir to the heir of different religions in the Compilation of Islamic Law and to know the judges regarding the consideration was borrowed to decide Case Number: 2/Pdt.G/2011/ PA.Kbj. The method used is normative with descriptive analytical research specifications. The types and sources of data consist of primary data that interview, while secondary data is literature and analyzed using qualitative analysis. The results showed that the position of the heirs of different religions in the Inheritance Law Islam does not recognize the existence of the heir to the person of a different religion (non-Muslim), for the purpose of inheritance itself according to the concept of maqasid al-shariah (the purpose of the revelation of Islamic law) operationally is to maintaining wealth and offspring. Basic consideration of the judge in determining the division of inheritance heir to the heir Muslims non-Muslims through was borrowed, which stated that the heirs who are not Muslims can still get the same share of the property with girls section partly heir.